ANALISIS SIMULASI PROTOKOL ROUTING DINAMIS OSPF UNTUK PENINGKATAN EFISIENSI JARINGAN HYBRID KAMPUS UNUD DENPASAR - Anjeli Sitanggang, Feybe; Wiharta, Dewa Made; Diafari Djuni H, I G A K (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUM, 2024)
UNUD GDLN building located in UNUD Sudirman campus acts as an information and communication technology service center as an internet access service provider, radio broadcast and online learning. The UNUD Campus network currently uses a static hybrid routing protocol, where the static routing protocol has the disadvantage that the network administrator must always reconfigure the network if there is a topology change. The Open Shortest Path First (OSPF) dynamic routing protocol can be used as a solution to overcome the weaknesses of static routing protocols because it is more suitable for larger networks and has the advantage of automatically determining the best route. This research aims to analyze the application of OSPF routing protocol in UNUD Denpasar Campus with GNS3 simulation. This research uses Quality of Service (QoS) parameters to analyze network performance, and test scenarios by PING with large data transmission that imitates YouTube video streaming. The results showed that OSPF dynamic routing protocol has better performance and has met the TIPHON standard with very good results for packet loss, throughput, and delay parameters and good results for jitter parameters. Tests on static routing protocol simulations and OSPF routing protocols are carried out by comparing the transmission process based on the resolution on YouTube video streaming imitation, starting with 360p, 480p, 720p and 1080p resolutions. Based on the results of the study, it can be concluded that OSPF routing is more suitable and produces better parameter values when transmitting streaming video with a resolution of 480p, 720p and 1080p, while the transmission of streaming video with a resolution of 360p is more suitable for static routing which is more suitable for transmission with lower resolutions.